Harm caused by the use of lisdexamfetamine to increase the academic performance of medical students: integrative review - Bacos , Beatriz Gordilho; Bergamini , Valentina Colombo; Rodrigues, Frank Menezes; Marini, Danyelle Cristine; Alves dos Santos, Cleidivan; Almeida Viana, Bianca Lorayne de; Vasconcelos, Ana Paula de; Rodrigues , Francisco Sandro Menezes (Journal of Medical Residency Review, 2024)
Lisdexamfetamine (LIS) is a central nervous system stimulant used to treat Attention-deficit/hyperactivity disorder (ADHD), improving attention, concentration and reducing hyperactivity. However, it is important to highlight that the National Health Surveillance Agency (ANVISA), the regulatory body for medicines in Brazil, does not recognize the efficacy and safety of LIS outside of its indications contained in the medicine leaflet and, in addition, the inappropriate use of this substance becomes a risk factor for the occurrence of anxiety, cardiac arrhythmias and glaucoma. This is an integrative literature review carried out in PubMed, LILACS and SciELO databases searching the descriptors “Lisdexamfetamine”, “ADHD”, and “Students”. Around 23.3% of medical students use these substances to overcome fatigue and improve performance, with Ritalin and Venvanse being the most common. However, 57.1% use these medications without a prescription or diagnosis of ADHD, obtaining them illegally. In general, all medications should only be used after medical evaluation and verification of real need, however, in the case of psychostimulants, caution must be even greater. Therefore, it is crucial to raise awareness among patients who are not diagnosed with ADHD about the long and short-term implications of self-medication with LIS, seeking to combat this public health problem.